Addiction Research Centres and the Nurturing of Creativity. (13th September 2013) - Tohyama, Tomomi; Yokoyama, Akira; Matsushita, Sachio; Higuchi, Susumu
Abstract The Kurihama Medical and Addiction Center began to conduct research and to provide medical care for alcohol‐related problems in 1963, when special alcoholism treatment wards were established in Japan for the first time. At first, the provision of medical care to patients was prioritized. However, training courses for specialists were initiated in 1975, and the Department of Clinical Research was established in 1984, which led to the formation of the present management structure in which the centre's staff are shared by three departments: Medical Care, Clinical Research and Education and Information. The Department of Medical Care provides specialized treatment for alcohol use disorders and medical services for other conditions, including behavioural addictions such as internet addiction and gambling disorder, as well as dementia and other psychiatric disorders. The Departments of Clinical Research and Education and Information are engaged mainly in specialized activities related to alcohol. The Department of Clinical Research conducts research on the epidemiology of alcohol use, the effects of alcohol on health and the treatment of alcohol use disorders in Japan, in cooperation with universities and other research institutions. The Department of Education and Information fosters the human capacity to achieve the primary, secondary and tertiary prevention of alcohol‐related problems and the dissemination of information on alcohol. The centre also performs alcohol‐related problem prevention activities, government consultations and international collaborative research and personal exchanges, thereby functioning as a central institution for alcohol policy‐based medical services and research in Japan.